2011
DOI: 10.1016/j.csda.2011.03.006
|View full text |Cite
|
Sign up to set email alerts
|

Optimal combination forecasts for hierarchical time series

Abstract: In many applications, there are multiple time series that are hierarchically organized and can be aggregated at several different levels in groups based on products, geography or some other features. We call these "hierarchical time series". They are commonly forecast using either a "bottom-up" or a "top-down" method. In this paper we propose a new approach to hierarchical forecasting which provides optimal forecasts that are better than forecasts produced by either a top-down or a bottom-up approach. Our meth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
382
0
8

Year Published

2017
2017
2024
2024

Publication Types

Select...
4
2

Relationship

2
4

Authors

Journals

citations
Cited by 342 publications
(444 citation statements)
references
References 37 publications
3
382
0
8
Order By: Relevance
“…We refer to (5) as the temporal reconciliation regression model. It is analogous to the cross-sectional hierarchical reconciliation regression model proposed by Hyndman et al (2011) and also applied in Athanasopoulos et al (2009) for reconciling forecasts of structures of tourism demand. A similar idea has been used for imposing aggregation constraints on time series produced by national statistical agencies (Quenneville and Fortier, 2012).…”
Section: Forecasting Frameworkmentioning
confidence: 99%
See 4 more Smart Citations
“…We refer to (5) as the temporal reconciliation regression model. It is analogous to the cross-sectional hierarchical reconciliation regression model proposed by Hyndman et al (2011) and also applied in Athanasopoulos et al (2009) for reconciling forecasts of structures of tourism demand. A similar idea has been used for imposing aggregation constraints on time series produced by national statistical agencies (Quenneville and Fortier, 2012).…”
Section: Forecasting Frameworkmentioning
confidence: 99%
“…is referred to as the "summing" matrix (drawing from the work of Hyndman et al 2011) and y [1] i is the vector of observations of the time series observed at the highest available frequency. It is not always possible to represent the aggregated series in a single tree such as Figure 1.…”
Section: Temporal Hierarchiesmentioning
confidence: 99%
See 3 more Smart Citations